The Laird rams Britain's ironclads built for the Confederacy, 1862-1923 - English, Andrew R. (McFarland & Company, Inc., Publishers, 2021)
"Built in Birkenhead, England, from 1862-1865, the "Laird rams" were two innovative armored warships intended for service with the Confederate Navy during the Civil War. The vessels represented a substantial threat to Union naval power, and offered the Confederacy a potential means to break the Union blockade of the Southern coastline. During 1863, the critical year of the Confederacy's last, slim hope of recognition by the British and French, President Lincoln threatened war with Britain if the ships ever sailed under Confederate colors. Built in some secrecy then launched on the River Mersey under the intense gaze of international scrutiny, the ships were first seized, and then purchased by Britain to avoid a war with the United States. These armored warships were largely forgotten after the Admiralty acquired them. Historians rarely mention these sister warships--if referred at all, they are given short shrift. This book provides the first complete history of these once famous ironclads that never fired a shot in anger yet served at distant stations as defenders of the British Empire"--